An insight into the intricacies of lingual paraphrasing pragmatic discourse on the purpose of synonyms - Jabir Al Nahian; Abu Kaisar Mohammad Masum; Muntaser Mansur Syed; Sheikh Abujar (Institute of Advanced Engineering and Science, 2022)
The term